Technology-Driven Archival Management in Samarinda's Library Service - Christiana, Novianti; Helminasari, Shorea; Pratama, Prawira Yudha (Indonesian Journal of Public Policy Review, 2024)
The management of archives is a critical function within governmental and private organizations, ensuring the preservation and accessibility of vital information. General Background: In response to the rapid advancements in information technology, the Government of Samarinda implemented a technology-based archival management system to improve efficiency and effectiveness. Specific Background: The study focuses on the implementation of this system within the Library and Archives Service of Samarinda, where traditional archival challenges such as the fragility of paper documents and the need for quick information retrieval necessitated a shift towards digital archives. Knowledge Gap: Despite the implementation of technology-based systems, there is limited research on their effectiveness within Indonesian governmental institutions. Aims: This study aims to evaluate the effectiveness of technology-based archival management in the Samarinda Library and Archives Service, focusing on document transfer, storage, indexing, and access control. Results: The findings indicate that the digital archival management system is effective in enhancing the security and accessibility of documents, with processes such as document scanning, digital storage, and indexing significantly improving archival practices. However, challenges such as inadequate storage capacity and network issues persist. Novelty: This study provides new insights into the specific challenges and successes of implementing a technology-based archival system in a governmental context in Indonesia. Implications: The research underscores the importance of continuous improvement in infrastructure and training to fully realize the benefits of digital archival systems, highlighting the need for enhanced server capacity and network reliability to support the increasing volume of digital archives. This study contributes to the broader understanding of digital archival management within the public sector, offering practical recommendations for similar initiatives in other regions. Highlights: Efficiency: Digital archives boost accessibility and security. Challenges: Storage and network issues hinder effectiveness. Implications: Ongoing infrastructure upgrades are essential. Keywords: Effectiveness, Archives, Digitalization, E-Archives